2013
DOI: 10.1103/physrevlett.111.197001
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Conductance Fluctuations Close to the Berezinskii-Kosterlitz-Thouless Transition in Ultrathin NbN Films

Abstract: We probe the presence of long-range correlations in phase fluctuations by analyzing the higherorder spectrum of resistance fluctuations in ultra-thin NbN superconducting films. The nonGaussian component of resistance fluctuations is found to be sensitive to film thickness close to the transition, which allows us to distinguish between mean field and Berezinskii-Kosterlitz-Thouless (BKT) type superconducting transitions. The extent of non-Gaussianity was found to be bounded by the BKT and mean field transition … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 39 publications
6
40
0
Order By: Relevance
“…Meanwhile, theoretical studies have revealed the ergodicity breaking [12] and the onset of out-of-equilibrium dynamics near T BKT [13]. However, except for a recent study of thin films of NbN [14], there have been no attempts, to the best of our knowledge, to probe the correlations in the BKT critical regime and the low-T phase. Furthermore, studies of the BKT physics in thin films of conventional superconductors, such as NbN, are complicated by the still not-well-understood relationship between film thickness, disorder, and superconductivity [15].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, theoretical studies have revealed the ergodicity breaking [12] and the onset of out-of-equilibrium dynamics near T BKT [13]. However, except for a recent study of thin films of NbN [14], there have been no attempts, to the best of our knowledge, to probe the correlations in the BKT critical regime and the low-T phase. Furthermore, studies of the BKT physics in thin films of conventional superconductors, such as NbN, are complicated by the still not-well-understood relationship between film thickness, disorder, and superconductivity [15].…”
Section: Introductionmentioning
confidence: 99%
“…We chose sputtered NbN as the material for this study for four main reasons: (a) It is widely researched, and experimental data collected for different growth methods and conditions are available; (b) there are contradicting reports about which of the existing models describes the T c suppression in NbN films-for instance, Kang et al [18] proposed that T c is suppressed due to the quantum size effect, Wang et al [17] suggested that the suppression follows Finkel'stein's model [9], Semenov et al [19] determined that the suppression is governed by the proximity effect, and Koushik et al [39] argued that the transition is of a BKT type; (c) the relatively high T c of NbN (16 K for a bulk NbN [40]) assists the experimental investigation; and (d) its properties make it useful for photodetectors [34,36,41,42].…”
mentioning
confidence: 99%
“…This, in turn, would introduce significant non-Gaussian components (NGCs) in the resistance fluctuations which can be experimentally probed by studying the higher-order statistics of the measured noise. To test whether the noise in this temperature range originates from glassy dynamics we calculated the fourth moment of voltage fluctuations, what is commonly known in as the "second spectrum" [39][40][41]. Physically, the second spectrum represents the fluctuations in the PSD with time in the chosen frequency octave.…”
Section: N Vmentioning
confidence: 99%
“…The details of the calculation method are given in Ref. [39]. The normalized value of the second spectrum σ (2) is given by…”
Section: N Vmentioning
confidence: 99%